Implementation of Child-Friendly School Policies: Evidence from Gowa, Indonesia - Muh Tahir Malik; Darti Darti (Al-Musannif, 2025)
Schools are expected to provide safe and supportive environments for children’s holistic development, yet gaps persist between Child-Friendly School (CFS) policy and practice in Indonesia, as evidenced by ongoing incidents of school violence. This study examines CFS implementation at a junior high school, while identifying supporting and constraining factors and their impact on the school environment. Using a qualitative case study approach, data were collected through interviews, participatory observation, and document analysis, and analyzed with Miles and Huberman’s model integrated with Edward III’s policy implementation framework. Findings indicate that clear communication, positive teacher dispositions, sufficient resources, flexible bureaucracy, and strong inter-organizational relations support effective CFS implementation, whereas limited funding, high student–teacher ratios, uneven understanding of CFS principles, and inconsistent parental involvement constrain it. CFS implementation has enhanced school cleanliness, reduced violence and bullying, and increased student participation. The study contributes theoretically by contextualizing Edward III’s model within CFS implementation and practically by providing strategies to strengthen CFS in similar contexts. Limitations include the single-case design and qualitative focus, suggesting the need for broader, mixed-method research in the future.